Study of boost converter using mosfet single phase matrix converter (SPMC) / Mohd Al Fadil Mat Nor - Mat Nor, Mohd Al Fadil (2010)
This paper presents a design and simulation of DC/DC boost converter operation of Single-Phase Matrix Converter (SPMC) using MOSFET as main power switching devices. The well-known Pulse Width Modulation (PWM) switching technique is used to control on and off of the SPMC circuit. Simulation model is developed using software Mentor Graphic to study the behavior of proposed technique. Selected simulation results are presented to verify the operation.